2021
DOI: 10.1016/j.ajp.2020.102509
|View full text |Cite
|
Sign up to set email alerts
|

Suicide during COVID-19 and other major international respiratory outbreaks: A systematic review

Abstract: Highlights This study reviews the literature on suicide during outbreaks, including COVID-19. Nine studies were included in the qualitative synthesis. Deducing an association between outbreaks and suicide is poorly supported. High-quality research would allow for a better understanding of this interrelation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 56 publications
1
38
0
1
Order By: Relevance
“…Concerningly, this study also documented Reddit users' perceptions about how their preexisting mental health challenges -including suicidal thinking -are being exacerbated in the pandemic context, with previous 'work' toward addressing mental health challenges and suicidal thoughts potentially being 'undone' by pandemic-related stressors. These findings align with literature from prior to the pandemic demonstrating that having a pre-existing mental health condition is a strong predictor for suicide (53)(54)(55), as well as more recent scholarship identifying baseline (i.e., pre-pandemic) mental ill health as a contributor to poor(er) mental health within the context of COVID-19 (3,56,57). More generally, findings from this study paint a complex picture illustrating associations between Reddit users' suicidal thoughts and various stressors amid the COVID-19 pandemic, suggesting that there are multiple and intersecting contributors to this experience.…”
Section: Discussionsupporting
confidence: 89%
“…Concerningly, this study also documented Reddit users' perceptions about how their preexisting mental health challenges -including suicidal thinking -are being exacerbated in the pandemic context, with previous 'work' toward addressing mental health challenges and suicidal thoughts potentially being 'undone' by pandemic-related stressors. These findings align with literature from prior to the pandemic demonstrating that having a pre-existing mental health condition is a strong predictor for suicide (53)(54)(55), as well as more recent scholarship identifying baseline (i.e., pre-pandemic) mental ill health as a contributor to poor(er) mental health within the context of COVID-19 (3,56,57). More generally, findings from this study paint a complex picture illustrating associations between Reddit users' suicidal thoughts and various stressors amid the COVID-19 pandemic, suggesting that there are multiple and intersecting contributors to this experience.…”
Section: Discussionsupporting
confidence: 89%
“…In the Czech Republic, the prevalence of suicide risk tripled from 3.9% in 2017 to 11.9% in 2020 [ 60 ]. However, a recent systematic review on suicidal outcomes during major international respiratory outbreaks, including COVID-19, found weak support for an association between pandemics, suicide, and suicide-related outcomes [ 65 ], underscoring the need for longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, suicide mortality rate increment is being observed as consistent with the prior pandemics (7). However, four major types of suicide stressors have been identified in the prior pandemics, whereas fear of being infected was regarded as the prominent suicide factor followed by social isolation, disruption of normal life, and burden of longterm illness (8,9).…”
Section: Introductionmentioning
confidence: 89%
“…However, four major types of suicide stressors have been identified in the prior pandemics, whereas fear of being infected was regarded as the prominent suicide factor followed by social isolation, disruption of normal life, and burden of longterm illness (8,9). In the context of the COVID-19 pandemic, fear of COVID-19 infection is also reported as the main suicide mediating factor (1,7,10,11). Studies have identified various domains of fear related to the fear of COVID-19 infection, such as fear of oneself or their family members getting infected, fear of having economic losses and being unemployed, or fear of avoidance behaviors toward gaining knowledge about the pandemic or fear of making decisions on showing or not showing actions like whether to visit parents or not, whether to look for information on death rates or not, etc.…”
Section: Introductionmentioning
confidence: 99%